A review of tillage effects on crop residue management, seedbed conditions and seedling establishment - Guérif, J; Richard, G; Dürr, C; Machet, J.M; Recous, S; Roger-Estrade, J (Soil & tillage research, 2001)
There is considerable discussion about the influence of soil management techniques on soil erosion, water use and conservation, and more recently carbon dioxide sequestration and waste disposal. The soil–atmosphere interface, particularly the seed bed layer is of particular concern to agronomists and soil scientists because it is the focus of the physical processes affecting crop establishment and biological activity. This paper evaluates the current knowledge (1) in modeling seedling emergence and residue decomposition, (2) seedbed structure and its resulting physical conditions, and (3) tillage operations affect on seedbed structure and residue distribution.